Pronunciation strategies used by EFL students - Hermida, Rita (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2022)
This study aims to figure out the strategies used by English as a foreign language (EFL) students to learn pronunciation. The study used questionnaire to collect the data. The study was carried out at an Islamic Boarding School in Greater Aceh, Aceh Province, Indonesia. The results of the study showed that the students predominantly used input/practice strategies, consisting of concrete experiences e.g., searching, listening, watching, and repeating sounds, to improve their pronunciation.